Such wicked intent - Oppel, Kenneth, 1967- (Oppel, Kenneth, 1967- Apprenticeship of Victor Frankenstein, 2012)
When his grieving father orders the destruction of the Dark Library, Victor retrieves a book in which he finds the promise of not just communicating with the dead, but entering their realm, and soon he, Elizabeth, and Henry are in the spirit world of Chateau Frankenstein, creating and growing a body.